Relation between serum calcium levels and mortality in patients with coronary artery disease. (24th May 2016) - Yan, Shao-di; Peng, Yong; Liu, Wei; Xia, Tian-li; Huang, Fang-yang; Chai, Hua; Huang, De-jia; Liu, Xiao-jing; Chen, Mao
Abstract: Objectives: Calcium has a critical role in a spectrum of biological processes related to cardiovascular disease. This study aimed to evaluate associations of baseline serum calcium levels with both short-term and long-term outcomes in CAD patients. Materials and methods: 3109 consecutive patients with angiography confirmed CAD, admitted to West China hospital of Sichuan University between July 2008 and September 2012 were enrolled and were categorized into quartiles according to admission serum calcium to determine the association of serum calcium level with in-hospital and long-term mortality by multivariable Logistic and Cox regression analysis respectively. Results: The admission serum calcium was normally distributed with a mean level of 2.20±0.15 mmol/L. A total of 259 deaths, including 58 in-hospital deaths, occurred during a mean follow-up of 20 months. Patients in the upper quartiles of serum calcium, as compared to the lowest quartile of serum calcium, were presented with lower in-hospital mortality [HR was 0.391 (95% CI: 0.188–0.812), 0.231(95% CI: 0.072–0.501) and 0.223 (95% CI: 0.093–0.534) for three upper quartiles versus lowest quartile respectively] and long-term mortality [HR was 0.614 (95% CI: 0.434–0.869), 0.476(95% CI: 0.294–0.698) and 0.553 (95% CI: 0.349–0.777) respectively]. Similar association between serum calcium and long-term mortality as showed in total cohort were also obtained when restricting analyses to subgroups: stable CAD patients, ACS patients and discharged patients. Conclusions: As a widely available clinical index, serum calcium was an independent predictor of both in-hospital and long-term mortality among CAD patients. Further studies are warranted to determine mechanisms and whether patients with hypocalcaemia could benefit from calcium supplement.